2016
DOI: 10.7584/ktappi.2016.48.1.075
|View full text |Cite
|
Sign up to set email alerts
|

Changes of BCTMP Fibers and Handsheets Properties by the Treatment of LB DES at Different Molar Ratios

Abstract: This study was conducted to investigate the effects of deep eutectic solvent (DES) treatment on BCTMP fibers and handsheets properties. DES was prepared using lactic acid and betaine (LB), and the molar ratio of these two components mixtures was controlled to 2:1 (LB 2:1) and 5:1 (LB 5:1). As results, 2% of BCTMP pulp (o.d. weight) was extracted when it was treated by LB 5:1 at 50℃ for 12 hours, stirring constantly at 120 rpm. In contrast, lignin was not extracted when BCTMP was mildly treated by the LB DES mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Choi et al (2016a) reported that the bulk of TMP handsheets decreased with DES treatment. Another study (Choi et al 2016b) noted that the bulk of BCTMP and BKP handsheets increased with DES treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al (2016a) reported that the bulk of TMP handsheets decreased with DES treatment. Another study (Choi et al 2016b) noted that the bulk of BCTMP and BKP handsheets increased with DES treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al (2016a) investigated the effects of DES (lactic acid and betaine) treatment on the properties of thermomechanical pulp (TMP) fibers and their handsheets. In another study (Choi et al 2016b), they investigated the effects of DES (lactic acid and betaine) treatment on bleached chemi-thermomechanical pulp (BCTMP) and bleached kraft pulp (BKP) fibers and their handsheets properties. Majová et al (2017) described the effect of DES on the delignification of hardwood kraft pulps having different lignin contents.…”
Section: Introductionmentioning
confidence: 99%
“…The rising importance of DES can be observed from the increasing publication number in the last decade from the Web of Science (2023) (Figure 1). During the last decade, DESs have been extensively studied in biomass fractionation (Li et al, 2017;Pan et al, 2017;Xu et al, 2018;Lyu et al, 2018;Kwon et al, 2020;Yan et al, 2023) and pulping (Choi et al, 2016a;2016b;Smink et al, 2019;Gülsoy et al, 2022a;2022b;Gülsoy, 2023).…”
Section: Introductionmentioning
confidence: 99%